2000
DOI: 10.1902/jop.2000.71.4.625
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and Implant Failure: An Exploratory Case‐Control Study

Abstract: This exploratory study suggests that a simple visual assessment of bone quality at the site of implant placement may be more informative regarding implant failure than pDEXA bone density measures obtained at peripheral bones. In order to determine whether peripheral osteoporosis measurements have a small or moderate association with implant loss, studies with larger sample sizes will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
1
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 21 publications
0
71
1
14
Order By: Relevance
“…Although the prevalence of osteoporosis increases with age and after menopause, the literature reviewed does not show the relationship of the implant failure rate with age and sex. The tactile valuation of bone quality during the preparation of the implant area, and the already achieved primary stability, bring more information that densitometric measurements of peripheral bones about the probability of failure (9).…”
Section: Implants In Subjects With Osteoporosismentioning
confidence: 99%
“…Although the prevalence of osteoporosis increases with age and after menopause, the literature reviewed does not show the relationship of the implant failure rate with age and sex. The tactile valuation of bone quality during the preparation of the implant area, and the already achieved primary stability, bring more information that densitometric measurements of peripheral bones about the probability of failure (9).…”
Section: Implants In Subjects With Osteoporosismentioning
confidence: 99%
“…Since osteoporotic patients require particular attention during implant placement, IT has been established as a simple and noninvasive method to assess local bone quality and primary implant stability. [10][11][12][13] It is the purpose of this study to test whether IT is significantly correlated with bone density or not, as assessed by the CBCT in a group of osteopenic and osteoporotic patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that primary stability is decreased at sites of low bone density, for example those in patients with osteoporosis, and this may be a risk factor for implant failure (3). Thus, bone density at the implant placement site appears to be a crucial factor that is correlated with failure rate and primary stability (4,5). In fact, osteoporosis patients who undergo implant treatment have a less favorable outcome than patients with healthy bone (6).…”
Section: Introductionmentioning
confidence: 99%